Communists, Cowboys, and Queers : The Politics of Masculinity in the Work of Arthur Miller and Tennessee Williams - Savran, David (Book collections on Project MUSE., 1992)
During the late 1940s and 1950s, argues David Savran, the baiting and brutalization of "communists and queers" were high on the national agenda. Within this historical context, Communist, Cowboys, and Queers offers a bold and radical reassessment of the works of theaters most prominent and respected figures - Arthur Miller, the alleged communist, and Tennessee Williams, the self-acknowledged "queer."Savran analyzes the radically different configurations of gender and sexuality in Millers and Williamss writings and studies the ways in which each confronted and negotiated the postwar homoph.